2004
DOI: 10.1023/b:jobb.0000041778.84464.16
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Characterization of Xenomitochondrial Mice

Abstract: Xenomitochondrial mice harboring trans-species mitochondria on a Mus musculus domesticus (MD) nuclear background were produced. We created xenomitochondrial ES cell cybrids by fusing Mus spretus (MS), Mus caroli (MC), Mus dunni (Mdu), or Mus pahari (MP) mitochondrial donor cytoplasts and rhodamine 6-G treated CC9.3.1 or PC4 ES cells. The selected donor backgrounds reflected increasing evolutionary divergence from MD mice and the resultant mitochondrial-nuclear mismatch targeted a graded respiratory chain defec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…While nuclear transfer technology has been employed since the mid-1990s to either clone or modify the genetic composition of mammals, a parallel genetic mechanism involves mitochondrial genetics using recently described techniques for mitochondrial transfer into embryos [11,23,27,28]. Development of cloned animals by nuclear transfer resulted in conflicting consequences when retrospective studies on mitochondrial transmission were reported [16,23,27].…”
Section: Discussionmentioning
confidence: 99%
“…While nuclear transfer technology has been employed since the mid-1990s to either clone or modify the genetic composition of mammals, a parallel genetic mechanism involves mitochondrial genetics using recently described techniques for mitochondrial transfer into embryos [11,23,27,28]. Development of cloned animals by nuclear transfer resulted in conflicting consequences when retrospective studies on mitochondrial transmission were reported [16,23,27].…”
Section: Discussionmentioning
confidence: 99%
“…Ease of manipulation of mouse embryos and genetics made the mouse an obvious choice for development of xenomitochondrial models of mitochondrial dysfunction. Injection of female M. m domesticus cybrid ES cells harboring mitochondria derived from an evolutionarily divergent murine species, M. terricolor , into blastocysts led to the creation of chimeric founder xenomitochondrial mice [7880]. Xenomitochondrial mice were produced by injection of 129S6/SvEvTac (129S6) ES cells harboring M. terricolor mtDNA into host C57BL/6NTac blastocysts, followed by breeding chimeric females to C57BL/6NTac males (B6NTac(129S6)-mt M. terricolor /Capt; line D7).…”
Section: Animal Modeling Of Mitochondrial Dysfunctionmentioning
confidence: 99%
“…Xenomitochondrial mice were produced by injection of 129S6/SvEvTac (129S6) ES cells harboring M. terricolor mtDNA into host C57BL/6NTac blastocysts, followed by breeding chimeric females to C57BL/6NTac males (B6NTac(129S6)-mt M. terricolor /Capt; line D7). This resulted in a maternal lineage of homoplasmic xenomitochondrial mice (designated “D7”) derived from cybrid ES cells, which was used in preliminary phenotypic characterization [28, 80]. …”
Section: Animal Modeling Of Mitochondrial Dysfunctionmentioning
confidence: 99%
“…However, progress is limited by the lack of mitochondrial DNA sequence information available for species other than the Mus musculus group and Rattus norvegicus. Therefore, to facilitate future studies, the mitochondrial genome of the Asian mouse species M. terricolor was sequenced; the mtDNA source used to create the first xenomitochondrial mice (McKenzie et al, 2004;Trounce et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…m. domesticus is the common inbred laboratory mouse of western European origin. It belongs to the Mus musculus species group that is comprised of the five subspecies M. domesticus, M. musculus, M. castaneus, M. molossinus and M. bactrianus (see Trounce et al, 2004). Interestingly, the mtDNA of these classic laboratory models is nearly identical and is believed to originate from a common M. m. domesticus maternal ancestor (Yonekawa et al, 1981;Ferris et al, 1982;Goios et al, 2007).…”
Section: Introductionmentioning
confidence: 99%